2019
DOI: 10.1111/rda.13606
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C treatment of embryos, but not donor cells, improves the cloned embryonic development in sheep

Abstract: Vitamin C is not only an antioxidant but also a regulator of epigenetic modifications that can enhance the activity of the ten‐eleven translocation (TET) family dioxygenases and promote the oxidation of 5‐methylcytosine (5mC) to 5‐hydroxymethylcytosine (5hmC). Here, we investigated the effects of vitamin C in regulating DNA methylation in sheep somatic cells or embryos in an effort to improve the cloned embryo development. Vitamin C treatment of sheep foetal fibroblast cells significantly increased the 5hmC le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…The latter are aimed at cardiovascular therapies and cardiosurgical treatments of a variety of cardioangiopathies [3,4]. In addition, the establishment of permanent cardiovascular stem cell clones that exhibit augmented stemness properties as a result of expressing the genotypic and phenotypic traits related to their tissue-specific genomic, epigenomic and proteomic profiles could also be valuable for the generation of nuclear donor cells for modern assisted reproductive technologies (ARTs) such as cloning sheep and other mammalian species by somatic cell nuclear transfer (SCNT) [77][78][79]. Future work in these areas is needed to address these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are aimed at cardiovascular therapies and cardiosurgical treatments of a variety of cardioangiopathies [3,4]. In addition, the establishment of permanent cardiovascular stem cell clones that exhibit augmented stemness properties as a result of expressing the genotypic and phenotypic traits related to their tissue-specific genomic, epigenomic and proteomic profiles could also be valuable for the generation of nuclear donor cells for modern assisted reproductive technologies (ARTs) such as cloning sheep and other mammalian species by somatic cell nuclear transfer (SCNT) [77][78][79]. Future work in these areas is needed to address these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…This study has demonstrated for the first time insightful and strongly evidence-based recognition of LPA-induced mechanisms underlying and identification of Hippo/YAP signaling pathway-related factors affecting not only onset and acceleration of blastocyst formation but also promotion of blastomere commitment and differentiation to ICM and TE cell lineages in bovine in vitro fertilization (IVF)-derived embryos. As a consequence, the LPA-triggered and Hippo/YAP pathway-mediated approaches could be widely applied to expedite the blastocyst formation by mammalian embryos that have been generated using other assisted reproductive technologies such as somatic cell nuclear transfer (SCNT) [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first attempts to generate cloned embryos by blastomere separation and embryo bipartition were carried out in sheep, as was the generation of embryos by SCNT [8]. SCNT is a biotechnology with great potential in the reproduction of sheep with high genetic value [9], to conserve endangered wild sheep [10] and to generate transgenic sheep with biomedical purposes [11].…”
Section: Of 15mentioning
confidence: 99%